(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2025)
The transportation problem is one of the most important optimization problems in economics and logistics. This article defines the optimal solution to the transportation problem. The goal is to minimize total transportation costs or maximize prof-its.